Data from: Global pattern of nest predation is disrupted by climate change in shorebirds - Kubelka, Vojtěch; Šálek, Miroslav; Tomkovich, Pavel; Végvári, Zsolt; Freckleton, Robert P.; Székely, Tamás (2018)
Ongoing climate change is thought to disrupt trophic relationships, with consequences for complex interspecific interactions, yet the effects of climate change on species interactions are poorly understood, and such effects have not been documented at a global scale. Using a single database of 38,191 nests from 237 populations, we found that shorebirds have experienced a worldwide increase in nest predation over the past 70 years. Historically, there existed a latitudinal gradient in nest predation, with the highest rates in the tropics; however, this pattern has been recently reversed in the Northern Hemisphere, most notably in the Arctic. This increased nest predation is consistent with climate-induced shifts in predator-prey relationships.